Public governance vs good governance: Outlining the concepts - Mohd Yusof, Muhamad Suhaimi; Romle, Abd Rahim; Mohd Kamal, Khirul Azwan (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
The transformation of public sector has been changed all over the world since last quarter of twentieth century.The rapid changes in the public sector are due to the globalizations demands and complexity in the fast-changing world. Thus, the changes had led to the rise of the corporate governance in the public sector which had changed the future of the public sector itself and growth as well.The changes in the public sector had strengthened the core and functions of the public sector at the same time.Hence, the rise of the corporate governance had response to the failure, incompetent, corruption and efficient as well. This paper will examine the elements in the governance which focus on two points in the corporate governance; public governance and good governance.The corporate governance in the public sector can be seen in the elements of public governance and good governance which had changed the perspectives of public management entirely